OCULAR GNATHOSTOMIASIS IN A FARMER FROM SOUTH SULAWESI, INDONESIA - Trisnawaty, Dian; Umar, Batari Todja (Majalah Oftalmologi Indonesia, 2025)
Introduction: Ocular Gnathostomiasis is a rare parasitic infection caused by the third-stage larvae of the spiruroid nematode. Gnathostome species are mostly seen in tropical and subtropical areas. It is a food-borne zoonosis caused by the consumption of raw or undercooked freshwater of fish, amphibians, reptiles, birds, and mammals, all of which are known to harbor the larval stages of Gnathostome species.   Case Report: A 37-year-old farmer complained of seeing moving objects in his left eye accompanied by blurred vision. At the previous visit, the patient had a history of red left eye with increased intraocular pressure, a visual acuity (VA) of 20/30 with the best corrected visual acuity (BCVA) of 20/20 and normal intraocular pressure. Slit lamp examination showed slight hyperemia of the conjunctiva and a live worm moving in the anterior chamber (AC). The worm was immediately removed using corneal clear incision and sent for parasitological examination.   Discussion: Ocular Gnathostomiasis by third-stage larvae of spiruroid nematode was found at the eye of a man from Siwa, South Sulawesi. Patients with complaints of recurrent redness of the eyes accompanied by increased intraocular pressure and a history of living in an area with a habit of eating raw freshwater fish should be considered the possibility of harboring helminth in the eye.   Conclusion: Patients with complaints of recurrent eye redness increased intraocular pressure, and a history of living in an area with a habit of eating raw freshwater fish should be considered the possibility of harboring helminth in the eye especially Gnathostome.